Political Imaging, Power, and Legal Accountability: A Normative Analysis - Sutawijaya, Darmawan (Ipso Jure, 2025)
Political imaging is an inseparable phenomenon from the dynamics of modern democracy in Indonesia. Through imaging, political actors seek to build public legitimacy in order to gain and maintain power. However, in practice, political imaging often exceeds the legal boundaries by adopting manipulative practices such as spreading hoaxes, vote buying, or misusing state facilities. This situation raises two fundamental questions: how the role of political imaging can be understood from the perspective of Indonesia’s positive law, and what forms of legal accountability should apply when such practices contradict legal norms and the ethics of governance. This study aims to analyze the role of political imaging within the framework of positive law and examine mechanisms of legal accountability for such violations. The method employed is normative legal research using statutory and conceptual approaches, supported by an analysis of current phenomena such as the rise of public demonstrations expressing dissatisfaction with the discrepancy between political imagery and policy reality. The findings indicate that political imaging is legally legitimate as long as it complies with electoral regulations and the principles of clean governance. However, when misused, accountability may take the form of administrative, criminal, ethical, or political sanctions. Public demonstrations are thus interpreted as a form of social correction and political accountability exercised by the people, highlighting the importance of enforcing the rule of law to ensure that political imaging truly serves as a healthy democratic communication tool.